The determinants of local government financial imbalance: a preliminary analysis - Ribeiro, Nuno A. (2019)
This research resulted from a theoretical framework, with special focus on financial imbalance in local government, studying the determinants of that imbalance. All Portuguese local authorities were analysed for the period 2014 to 2016, by testing the empirically formulated research hypotheses using the econometric model of logistic regression. The results obtained show that a larger population under 15 years old and over 65, financial independence, transfers from central government and investment expenditure are less likely to produce situations of financial imbalance in local authorities. Political ideology, the existence of political alternation in government and local authorities with greater capital income and greater expenditure on staff are the explanatory variables of municipal financial imbalance. No statistical evidence was found for the variables of population size, population density, location, purchasing power index and form of governance.